2017
DOI: 10.5530/jyp.2017.9.50
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Custom Officers on Counterfeit Pharmaceutical Products And The Roles Of Pharmacy Enforcement Officers

Abstract: Background: Counterfeit pharmaceutical products (CPP) is a lucrative business for illegal operators who constantly try to smuggle their products into Malaysia. Full understanding of the roles and duties of pharmacy enforcement division as well as CPP by Royal Malaysian Custom (RMC) officers are pre-emptive to optimize the operation against drug smuggling. Objective: This study is aimed to examine the awareness of RMC officers on CPP and the roles of Pharmacy Enforcement Division (PED) officers at custom ports.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In line with this result, the results of the study by Tink indicated that knowledge of Malaysian customs o cials about counterfeit pharmaceutical products and the role of pharmacy executives were su cient to prevent the entry of smuggled pharmaceutical products through the cooperation of pharmacy o cers (12). Gaudiano, in line with the present study's ndings, showed that immediate intermittent action is needed through the collaboration of o cial drug control laboratories, health o cials, police forces, professional organizations, and consumer associations (13). Consistent with the present paper, Garuba also showed that Nigeria's pharmaceutical system's pillars are relatively vulnerable to corruption.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with this result, the results of the study by Tink indicated that knowledge of Malaysian customs o cials about counterfeit pharmaceutical products and the role of pharmacy executives were su cient to prevent the entry of smuggled pharmaceutical products through the cooperation of pharmacy o cers (12). Gaudiano, in line with the present study's ndings, showed that immediate intermittent action is needed through the collaboration of o cial drug control laboratories, health o cials, police forces, professional organizations, and consumer associations (13). Consistent with the present paper, Garuba also showed that Nigeria's pharmaceutical system's pillars are relatively vulnerable to corruption.…”
Section: Discussionsupporting
confidence: 82%
“…Tra cking is a multidimensional issue, and it is necessary to identify its various challenges and causes and to consider interventions at different levels. Numerous studies have been conducted on drug tra cking (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In these studies, the black market and drug tra cking have been emphasized, and it has been stated that more effective control is needed to prevent the black market of drugs (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This division also acts as technical advisors for the Royal Malaysian Customs (RMC) regarding pharmaceutical products. 26 These authorities play important roles in controlling the influx of THM products into the country. Since more than half (55%) of the adulterated THM products identified in this study originated from other countries, mainly from Indonesia and China, there is a need for a stricter entry requirement by the authorities for THM products into the country.…”
Section: Discussionmentioning
confidence: 99%
“…The penalties for failing to keep any book or register or any false entry will be indictable by a fine not more than 5000 ringgit or custody not more than two years or both. An individual who is charged for offending this Act is indictable by a fine not more than 3000 ringgit or custody, not more than 1 year or both [29].…”
Section: Inspection and Penaltiesmentioning
confidence: 99%